Internal-Control Willingness and Managerial Overconfidence - Bin Liu (Frontiers Media S.A., 2021)
Internal control is a branch of accounting subject, and accounting control and risk management are the core of enterprise internal control. Previous studies have shown that high-quality internal control inhibits or regulates managerial overconfidence (MOC). However, it is believed that the influential factors of internal-control quality (ICQ) are normally objective factors, such as corporate characteristics, financial status, and governance structure. Corresponding to another type of constituent element, that is, the subjective factor, which we called internal-control willingness, has not been explored. In this study, we defined internal-control willingness as the degrees of the subjective initiative of the internal-control construction and execution activities of enterprises. In addition, we proposed a method to measure internal-control willingness based on text analysis and principal component analysis using Python, and then, we tested its impact on ICQ and MOC. Our findings are as follows: (A) internal-control willingness has a positive impact on ICQ, and (B) internal-control willingness lowers MOC. Our study introduces subjective initiative factors into the field of internal control and also extends the understanding of internal-control theory. Based on empirical conclusions, we suggested that regulatory authorities and corporate boards improve incentive mechanisms to jointly strengthen the internal-control willingness of all employees, so as to help enterprise managers operate rationally.